2014
DOI: 10.1097/ccm.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence During Brain Death Evaluation

Abstract: Family presence during brain death evaluation improves understanding of brain death with no apparent adverse impact on psychological well-being. Family presence during brain death evaluation is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 33 publications
2
53
0
4
Order By: Relevance
“…This is in opposition with studies reporting family satisfaction, with an improvement of post-traumatic stress disorders, when they participated in comfort care [28], when they were present during brain death evaluation [29] or even during cardiopulmonary resuscitation [30]. Satisfaction and well-being of families in participation of care could be induced by giving a bedside role, by favoring the link with the loved one, and thus having the family feeling useful for the ICU staff.…”
Section: Discussionmentioning
confidence: 70%
“…This is in opposition with studies reporting family satisfaction, with an improvement of post-traumatic stress disorders, when they participated in comfort care [28], when they were present during brain death evaluation [29] or even during cardiopulmonary resuscitation [30]. Satisfaction and well-being of families in participation of care could be induced by giving a bedside role, by favoring the link with the loved one, and thus having the family feeling useful for the ICU staff.…”
Section: Discussionmentioning
confidence: 70%
“…For example, Tawil et al recently conducted a small randomized trial demonstrating that family presence during brain death evaluation has the potential to improve understanding of brain death without causing psychological harm at 30 and 90 days. 85 …”
Section: Resultsmentioning
confidence: 99%
“…, Twail et al . ). Participant responses demonstrated that the right of families to be present conflicted with the routines of care and illustrated the influence of the professional and environmental context and culture.…”
Section: Discussionmentioning
confidence: 97%